Applying the scores of multivariate statistical analyses to characterize the relationships between the hydrochemical properties and groundwater conditions in respect of the monsoon variation in Kapas Island, Terengganu, Malaysia - Mohd Isa, Noorain; Aris, Ahmad Zaharin; Narany, Tahoora Sheikhy; Sulaiman, Wan Nor Azmin (Springer, 2017)
The different factors (seasonal changes) and variables (physicochemical) controlling the groundwater hydrochemistry of Kapas Island were identified using multivariate techniques principal component analysis (PCA), discriminant analysis (DA) and hierarchy cluster analysis (HCA). In the present study, the hydrochemistry of 216 groundwater samples, consisting of information concerning the in situ parameters and major ions in six monitoring boreholes, was studied and compared in two different monsoon seasons. The dominant variables derived from four components by PCA in the pre-monsoon indicated the influence of the salinity process, while the dominant variables derived from three components in the post-monsoon mostly indicated on the mineralization process. The DA gave the final variables after discriminating the insignificant variables based on the pre- and post-monsoon classifications. This provided important data reduction in terms of the mineralization process, as it only discriminated physical variables (TDS, EC, salinity, DO and temperature). Based on the HCA result, samples belonging to stations KW 3 and KW 4 were under Ca-rich water, while the remaining boreholes were grouped in Na-rich water.